Involvement of miR‐145 in the development of aortic dissection via inducing proliferation, migration, and apoptosis of vascular smooth muscle cells. Issue 1 (6th September 2019) - Huang, Wenhui; Huang, Cheng; Ding, Huanyu; Luo, Jianfang; Liu, Yuan; Fan, Ruixin; Xiao, Fei; Fan, Xiaoping; Jiang, Zhisheng
Abstract: Aim: The current study aimed to examine miR‐145's contribution to thoracic aortic dissection (AD) development by modulating the biological functions of vascular smooth muscle cells (VSMCs). Methods: The concentration of circulating miR‐145 was determined in patients with AD and healthy controls using quantitative polymerase chain reaction (qPCR). Aortic specimens were obtained from both individuals with Stanford type A AD undergoing surgical treatment and deceased organ donors (serving as controls) whose causes of death were nonvascular diseases. Then, qPCR and fluorescence in situ hybridization were applied to assess miR‐145 amounts and location, respectively. Furthermore, qPCR and immunoblot were employed to determine SMAD3 (the target gene of miR‐145, involved in the TGF‐β pathway) amounts at the gene and protein levels, respectively. Moreover, in vitro transfection of VSMCs with miR‐145 mimics or inhibitors was conducted. Finally, the 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay, Transwell assay and flow cytometry were employed for detecting VSMC proliferation, migration, and apoptosis, respectively. Results: The amounts of miR‐145 in plasma and aortic specimens were markedly reduced in the AD group in comparison with control values ( P < .05). miR‐145 was mostly located in VSMCs. Proliferation and apoptosis of VSMCs were significantly induced in vitro by the downregulation of miR‐145. Also, miR‐145 modulated SMAD3 expression. Conclusions: miR‐145 was found to be downregulated in patients with AD, which induced the proliferation, migration, and apoptosis of VSMCs by targeting SMAD3. This suggested the involvement of miR‐145 in the pathogenesis of AD.